All-Inorganic Perovskite CsPb2Br5 Microsheets for Photodetector Application - Tang, Xiaosheng; Han, Shuai; Zu, Zhiqiang; Hu, Wei; Zhou, Dan; Du, Juan; Hu, Zhiping; Li, Shiqi; Zang, Zhigang (Frontiers in Physics, 2018)
Lead-halide perovskites have emerged as one kind of important optoelectronic materials with excellent performance in photovoltaic and light-emitting diode applications. Herein, we reported all-inorganic perovskite CsPb2Br5 microsheets prepared by a facile injection method. Through the X-ray diffraction (XRD) and Scanning Electron Microscope (SEM), it could be seen that the CsPb2Br5 microsheets showed single tetragonal crystalline phase and kept uniform square shape. Moreover, the as-synthesized CsPb2Br5 microsheets exhibited photoluminescence emission at 513 nm, and the UV–vis absorption spectrum further indicated the band gap of CsPb2Br5 microsheets was ≈2.50 eV. Additionally, the as-fabricated CsPb2Br5 microsheets based photodetector exhibited faster photoresponse characteristics of short rise time (0.71 s) and decay time (0.60 s), which demonstrated its promising application as high performance electronic and optoelectronic devices.